Preparation, characterization and adsorption performances prepared from corn cob for removal of dye solutions - Sukanya A/P Ramaiah (School of Environmental Engineering, University Malaysia Perlis, 2012)
The objective of this study was to investigate the removal of Methylene Blue (MB) and Methyl Orange (MO) dyes from synthetic wastewater by the adsorption on treated and untreated corn cob adsorbents. Surface morphology was examined using Scanning Electron Microscopy (SEM). The chemical composition, elemental analysis and functional groups of the surface were conducted using Fourier Transform Infrared (FT-IR) techniques, respectively. Batch adsorption experiments were carried out to find out the effects of contact times, initial dye concentrations (50 mg/L - 500 mg/L), and pH (2 -13) on the adsorption of the dye by both untreated and treated adsorbents. The results of the experiment showed that from initial dye concentration of 50 mg/L, the adsorption of dye was rapid in the first hour till 8 hour of contact time and equilibrium is reached in about 24 hour for both untreated and treated adsorbents, respectively. About 90% the dye was removed by treated adsorbent at its equilibrium contact time. The experimental isotherms data were analyzed using Langmuir and Freundlich isotherm models. The data was found that Freundlich isotherm model fits the data very well for all two dyes on both adsorbents. The calculated dimensionless separation factor, R indicated that the adsorptions of the two dyes onto both adsorbents were favorable. Pseudo-first order and pseudo-second order kinetic equations were used to examine the experimental data of different initial concentrations. It was found that the pseudo-first order kinetic equation described the data of dyes adsorption on both adsorbents very well. Thermodynamic parameters, such as Gibbs energy (G), enthalpy change (H) and entropy change (S), were calculated, which indicated that the presence system was non spontaneous and exothermic process for MB and MO.